Business Cycles and FDI: Evidence from German Sectoral Data - Claudia M. Buch; Alexander Lipponer (Kiel Institute for World Economics (IfW), 2005)
Globalization has affected business cycle developments in OECD countries and has increased activities of firms across national borders. This paper analyzes whether these two developments are linked. We use a new firm-level dataset on the foreign activities of German firms to test whether foreign activities are affected by business cycle developments. We aggregate the data by the sector of the reporting firm, the sector of the foreign affiliate, and the host country. Data are annual and cover the period 1989- 2002. We find that German outward FDI increases in response to positive cyclical developments abroad and in response to a depreciation of the domestic currency.
Keywords: E3; F23; 330; business cycles; multinational activity; FDI; panel regressions; Direktinvestition; Multinationales Unternehmen; Deutsch; Konjunktur; Abwertung; Kaufkraftparität; Euro; Schätzung; Welt; Deutschland